2012
DOI: 10.1002/asi.22616
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Publication Power Approach to Artificial Intelligence Journals

Abstract: This study evaluates the utility of a Publication Power Approach (PPA) for assessing the quality of journals in the field of artificial intelligence. PPA is compared with the Thomson-Reuters Institute for Scientific Information (TR) five-year and two-year impact factors and with expert opinion. The ranking produced by the method under study is only partially correlated with citation-based measures (TR), but exhibits close agreement with expert survey rankings. A simple average of TR and power rankings results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Examples include business and technical communication (Lowry, Humphreys, Malwitz, & Nix, 2007a), business ethics (Beets, Lewis, & Brower, 2016;Serenko & Bontis, 2009a), library & information science (Manzari, 2013), artificial intelligence (Rokach, 2012;Serenko, 2010), information systems (Chen et al, forthcoming), and knowledge management (Serenko & Bontis, 2009b). With this study, we further advance the pioneering attempt by Le Rouge and De Leo (2010) to understand researchers' perceptions of e-health journals.…”
Section: Academic Journal Rankingsmentioning
confidence: 90%
“…Examples include business and technical communication (Lowry, Humphreys, Malwitz, & Nix, 2007a), business ethics (Beets, Lewis, & Brower, 2016;Serenko & Bontis, 2009a), library & information science (Manzari, 2013), artificial intelligence (Rokach, 2012;Serenko, 2010), information systems (Chen et al, forthcoming), and knowledge management (Serenko & Bontis, 2009b). With this study, we further advance the pioneering attempt by Le Rouge and De Leo (2010) to understand researchers' perceptions of e-health journals.…”
Section: Academic Journal Rankingsmentioning
confidence: 90%
“…The behavior of these researchers can be trusted because they have demonstrated a level of research excellence which is recognized by their peers (who have participated in their tenure and promotion committees). Rokach [16] has shown that the publication power approach (PPA) that was developed by [5] for identifying the premier journals can reliably rank AI journals.…”
Section: Journal Rankingsmentioning
confidence: 99%
“…Unlike the results of stated preferences from opinion surveys, or other forms of subjectivity, publication power is based on actual behaviors. Examples of studies adopting the power approach include those of Dees (), Holsapple (), Holsapple and O'Leary (), Holsapple and Lee‐Post (); Rokach (), Serenko and Jiao (), and Song (). Power measures involve the identification of an independently selected set of prominent researchers whose publishing behaviors are to be studied.…”
Section: Basic Directions For Measuring Knowledge Disseminationmentioning
confidence: 99%
“…Each PI variant has been designed by building on the traditional bibliometric impact measure of citations (Harzing & van der Wal, ), and on the bibliometric power concept (Rokach, ). By integrating the two approaches into each PI variant, the analytics results reported here give greater holistic insight into relative statures of journals as knowledge‐dissemination channels in the IS field.…”
Section: Demonstration Of the Pi Techniquementioning
confidence: 99%
See 1 more Smart Citation